Red Rice (Oryza Nivara) Growth and Yield are Impacted by Seedling Age and the Concentration of Liquid Organic Fertilizer - Yanvar Bestar, Ade; Jaenudin, Amran; Setya Wahyu Atmaja, Ida (Jurnal Agrosci, 2023)
This study aims to ascertain how seedling age and liquid organic fertilizer content interact and correlate with red rice growth and production. This study was conducted in Karya Mulya village, Kesambi district, Cirebon, West Java, from December 2020 to April 2021. The factorial randomized block design (RBD) research methodology was used. Plant height, tiller count, leaf color, number of active tillers, number of panicles per clump, panicle length, number of grains per panicle, weight of 1000 grains, dry weight of grain harvested per plot, and dry weight of grain milled per plot were the key observations. The findings indicate that at 35 days following planting, there was an interaction between seedling age and liquid organic fertilizer concentration on leaf greenness. While the number of tillers 35 days after planting was affected by seedling age independently. When applied 42 days after planting, liquid organic fertilizer had an impact on the number of productive tillers, the number of panicles per clump, the length of the panicle, the number of grains per panicle, the weight of 1000 grains, the dry weight of the grain harvested per plot, and the dry weight of the grain ground per plot.